Qualidade de vida da pessoa surda no ambiente familiar - Garcia, Renata Rodrigues de Oliveira (2016)
A dissertation includes scientific paper mode. The first article entitled, "Deafness, family and health: experience report" aimed to describe the personal experience lived by the author in the family context. It is a qualitative research, and a reporting experience type, carried out based on the description of personal experience, which consists of real-life stories. In this case, the focus is my life as a daughter, deafness in a family context that valued the oral rehabilitation, believing in a biomedical approach, disregarding the social and cultural aspects of deaf people. The results show that prior to the enactment of the Act No. 10.436 and Decree No. 5.626 of Brazilian Sign Language (Libras), my family found difficult to accept Sign Language (SL), in consequence, it created barriers in communication and inferiority feelings. The acceptance promoted improvement in personal and professional life. The concept of deaf people must be accompanied by recognition and acceptance of the linguistic values of the deaf community and SL. In the second article, entitled "Quality of life of deaf people who communicate by Sign Language in the family environment" it aimed to characterize the Quality of Life (QOL) of deaf people with regard to aspects as discrimination, autonomy and inclusion. In addition, it aimed to compare, on a family environment, the Quality of Life related to health (QOLRH) of deaf people and their listeners siblings, with regard to physical, psychological, social relationships and environment. It is a cross-sectional, descriptive and quantitative study carried out with 194 participants, which were the deaf people and their listeners siblings residing in Brazil and abroad. The inclusion criteria were: age 18 years old; families who have deaf and hearing children; the deaf family member have to use the SL as means of communication; deaf and their siblings listeners from different regions of Brazil where they reside; deaf and siblings listeners who signed the Informed Consent (IC) in person or by sending the acceptance to participate in the survey by email. The deaf participants answered to questionnaires on QOL in Libras version. Among listeners siblings, questionnaires in Portuguese version were used on the same site. The results were: greater prevalence of female sex, divorced, with active working life and childless. Regarding to the earned income, 44% (deaf) had income up to a thousand and five hundred reais and 44.7% had income of more than a thousand and five hundred reais. The comparison of QOL among the deaf and their siblings listeners by WHOQOL-Bref/Libras showed that listeners had better scores in all areas, however, the physical domain was the one that showed a significant difference statistically (p = 0.033). The assessment of QOL of the deaf participants at WHOQOL- Dis/Libras showed better scores in Inclusion domain (72.5 ± 13.8). We conclude that in family environment, relations between siblings do not always occur harmoniously. The access to SL as the first language of deaf people should be guaranteed to all deaf people, and family require an adequate guidance about deaf culture and the SL. We verified the contribution of the study and how important it is to have questionnaires in Libras to evaluate the QOLRH of deaf people.